The influence of Environmental, Social, Governance (ESG) and leverage on the cost of capital (empirical study on mining companies listed on the Indonesia Stock Exchange for the 2022-2024 period) - Nia Yulianty; Rendi Kusuma Natita (Privietlab, 2026)
The primary objective of this investigation centers on evaluating the impact exerted by Environmental, Social, and Governance (ESG) factors together with leverage upon capital costs among mining corporations listed on the Indonesia Stock Exchange spanning the 2022–2024 interval. A quantitative methodology was employed, drawing upon secondary datasets sourced from audited annual reports, dedicated sustainability disclosures, and publicly available financial documentation. Through purposive sampling criteria, a cohort of 14 mining entities was delineated, yielding 42 firm-year observations for empirical scrutiny. ESG efficacy was quantified via a composite index aligned with Global Reporting Initiative (GRI) Disclosure Standards 2021, leverage was operationalized through the Debt-to-Equity Ratio (DER), and capital costs were proxied by the Weighted Average Cost of Capital (WACC). Rigorous preprocessing incorporated classical assumption validations, culminating in multiple linear regression analysis facilitated by IBM SPSS Statistics version 25. Empirical outcomes revealed that ESG disclosures manifest no discernible influence on capital costs, standing in stark juxtaposition to leverage, which demonstrated a negative and statistically robust association therewith. Collectively, ESG alongside leverage were found to significantly shape financing expenses, underscoring a synergistic explanatory mechanism. These results illuminate the preeminence of strategic debt management over sustainability signaling in modulating capital costs within Indonesia's mining landscape during the study window a nuance attributable to sectoral capital intensity and nascent ESG differentiation. By furnishing substantive evidence on the interplay of financial engineering and non-financial governance metrics, this inquiry enriches theoretical discourse on cost determinants within emerging market contexts, offering actionable insights for corporate treasurers navigating volatility-prone resource sectors.